2010
DOI: 10.1152/japplphysiol.00424.2009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aerobic exercise on tumor physiology in an animal model of human breast cancer

Abstract: JE 2nd, Dewhirst MW. Effect of aerobic exercise on tumor physiology in an animal model of human breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
119
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(131 citation statements)
references
References 39 publications
6
119
0
2
Order By: Relevance
“…In recent years, regular exercise has been demonstrated to considerably lead to inhibition of tumor growth and mitigation of metastatic expansion in animals and humans (25)(26)(27). In the present study, the tumor volume and tumor growth rate was decreased in the endurance training group, such that in the 10th week, tumor volume growth was 10.34 times greater than the first week, while in the control group, the corresponding rate was 12.13 times.…”
Section: Discussionsupporting
confidence: 45%
“…In recent years, regular exercise has been demonstrated to considerably lead to inhibition of tumor growth and mitigation of metastatic expansion in animals and humans (25)(26)(27). In the present study, the tumor volume and tumor growth rate was decreased in the endurance training group, such that in the 10th week, tumor volume growth was 10.34 times greater than the first week, while in the control group, the corresponding rate was 12.13 times.…”
Section: Discussionsupporting
confidence: 45%
“…Given that exercise is associated with increased cardiac output and regional changes in blood flow, the bioavailability of DOX to the tumor environment may have improved the potency of the drug. Jones et al found intratumoral vascularization increased in tumors taken from exercised mice compared with tumors from sedentary mice (22). Another possibility is that soluble factors found in plasma following exercise may inhibit tumor cell survival and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In support of our findings, several other investigations have also shown benefits of physical activity on breast cancer independent of changes in body composition (5,9,10). Therefore, additional hypotheses explaining the changes induced by voluntary wheel running may include alterations in energy sensing pathways, growth related proteins and/or myokines and cytokines (14,15,31). In fact, we have previously shown that treadmill exercise can reduce circulating levels of the inflammatory, pro-tumorigenic cytokines, MCP-1 and IL-6, in accordance with decreased tumor volume in C3(1)/SV40Tag mice (15).…”
Section: Discussionmentioning
confidence: 96%
“…Thompson et al (26) has consistently shown decreased carcinogenic incidence after both free and motorized wheel running in the chemicallyinduced rat model of mammary tumorigenesis (20,24,26). Conversely, benefits as well as no effect of exercise have been reported in mouse implantation models using MDA-MB-231 human breast cancer cells (14,25). However, chemical, implantation and hormone-induced cancer models may not accurately portray the development and progression of the human disease making it difficult to specifically assess the effects of exercise on disease initiation and progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation